Reconstructing Contemporary Islamic Education Curricula through Ibn Khaldun's Educational Philosophy: An Integrative Dialogue with Modern Curriculum Theory - Desi Fitria; Abdul Aziz; Muslihudin (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to reconstruct contemporary Islamic education curricula through Ibn Khaldun's educational philosophy by integrating its epistemological, pedagogical, and curricular principles with modern curriculum theory. Using qualitative library research, the study analyzed Al-Muqaddimah as the primary source alongside contemporary Scopus-indexed literature through content analysis and philosophical interpretation. The findings identify four interconnected curriculum pillars: epistemological integration between naqliyyah and aqliyyah, development of malakah as holistic competence, developmental curriculum organization based on al-tadrij and takrar, and dialogical learner-centered pedagogy. These findings demonstrate that Ibn Khaldun's educational philosophy provides a more comprehensive curriculum reconstruction framework than previously recognized, challenging the assumption that his contribution is primarily historical. This study strengthens previous scholarship on Islamic educational philosophy, questions the dichotomy between religious and secular knowledge, and introduces the Integrative Islamic Curriculum Framework as a novel conceptual model linking classical Islamic educational philosophy with integrated curriculum, competency-based education, developmental curriculum theory, and constructivist learning. The framework provides a theoretical foundation for curriculum reform, educational policy, and future empirical studies supporting holistic, ethical, and digitally responsive Islamic education.